Development and application of a user-friendly general-purpose predictive simulation tool for two-dimensional flow analysis. (May 2023) - Eum, Tae-soo; Seo, Il Won; Shin, Eun-taek; Song, Chang Geun
Abstract: Flow analysis model is useful in designing hydraulic structures, understanding hydraulic processes, and predicting the impacts of development works and natural events. Accordingly, needs for hydraulic models that can accurately simulate hydraulic phenomena in natural and engineered rivers are increasing. Here, HDM-2Di, a predictive two-dimensional flow simulation model, was developed and integrated in RAMS+, a mesh generation and visualization tool. RAMS + has intuitive user interface in generating and editing meshes, and setting boundary conditions. With the geometry construction module RAMS-G, river cross-sections and bank stations can be automatically extracted by applying linear interpolation-based spatial functions to the generated mesh. The tool was applied to a meandering experimental flume and a natural river to evaluate its accuracy. The tool was able to successfully reproduce observed flows in channel and river. RAMS+ is currently downloadable at www.ramsplus.net . Detailed tutorials, a user guide, and examples are also provided. Highlights: HDM-2Di, a predictive simulation model for 2D flow, was developed and integrated with RAMS+, a user-friendly tool for mesh generation (RAMS-G) and visualization (RAMS + GUI). With RAMS-G, it is possible to automatically extract river cross sections and bank stations by applying linear interpolation-based spatial distribution treatment to the generated mesh. Therefore, it enables 2D topographic data to be constructed more easily. Compared with existing 2D river analysis software, mesh generation and editing, integrating meshes with the simulation engine, and setting boundary conditions can be intuitively configured to increase usability.